Percutaneous Endovascular Abdominal Aortic Aneurysm Treatment, Complicated by Femoral Pseudo-Aneurysm: Tratamento de Aneurisma da Aorta Abdominal por PEVAR Complicado de Pseudo-Aneurisma Femoral - Sousa, Joel; Brandão, Daniel; Barreto, Paulo; Ferreira, Joana; Almeida-Lopes, José; Mansilha, Armando (Gazeta Médica, 2018)
Abdominal aortic aneurysm is a common and silent disease, with potentially tragic outcomes in case of rupture. Although in the past the treatment of this pathology always required complex surgical procedures, with great perioperative morbidity and mortality, the development of the endovascular aneurysm repair (EVAR) techniques, and their generalization as gold-standard procedures, completely revolutionized the current state of the art. Nowadays, and due to these techniques, it is possible to treat older patients as well as patients with higher surgical risk, previously deemed unfit for surgery. This is a case report of an 86 years old male, with multiple cardiovascular risk factors, diagnosed with an abdominal aortic aneurysm, and treated by EVAR with percutaneous access and under local anaesthesia. The procedure complicated with the development of a left femoral pseudo-aneurysm, which was successfully corrected in a minimally invasive fashion through percutaneous echo-guided injection of thrombin. Received 25/05/2016 - Accepted 06/06/2016